Techno-economic analysis of the valorisation of brewers spent grains: Production of xylitol and xylo-oligosaccharides - Swart, Lukas Johannes (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.